Implementing the Merdeka Curriculum through a Deep Learning Approach in Primary Education: A Case Study of SD Negeri 1 Cintarasa, Garut Regency - Fitri Eka Silviani; Ayu Puji Rahayu; Nurul Aziza; Ika Sartika (Journal of Asian Primary Education (JoAPE), 2025)
Curriculum reforms are continually implemented in Indonesia to improve the quality of national education and foster student-centered learning. One breakthrough is the implementation of the Merdeka Curriculum with a deep learning approach, which emphasizes meaningful, mindful, and joyful learning, thereby encouraging students to actively understand, apply, and reflect on their knowledge in ways that are relevant to their lives. This study aims to determine the understanding of school administrators and teachers regarding the concept of the Merdeka Curriculum based on deep learning and its implementation at SDN 1 Cintarasa. This study uses a descriptive qualitative approach to understand in depth the process of implementing the Merdeka Curriculum with a deep learning approach in the real context of school learning. Data collection was conducted using several techniques, namely observation, semi-structured interviews, and document analysis. These three techniques were used to strengthen the data through triangulation.